THE RELATIONSHIP OF DIET TO CHOLESTEROL LEVELS IN THE ELDERLY - Novalia Efrianty; Sari, Lisna Ferta Sari; Sari, Dwi Rima Septiani (Majalah Kedokteran Sriwijaya, 2024)
Cholesterol is a fat found in the bloodstream or in the cells of the body, which is actually needed for the formation of cell walls and as a raw material for some hormones, but if the cholesterol level in the blood is excessive, it will cause coronary heart disease and stroke. Most of the 80% cholesterol in the body is produced naturally in the liver. Meanwhile, a small portion of about 20% of cholesterol comes from foods consumed, such as products derived from animals, such as meat, eggs, and milk. The aim of this research is to find out how the relationship of dietary patterns and the level of cholesterol in the elderly work area of the Sukaraya Health Center. The research method uses quantitative type with analytic method. This research was conducted at the Sukaraya Health Center. The respondents of this research were 30 persons. This research utilized a cross sectional study to assess the relationship between the variables and this research used a instrument questionnaire. From the chi square statistical test the result shows that diet with cholesterol level has a p value of 0.001 (<005). It shows that there is a significant relationship between the diet and the level of cholesterol in the elderly in the working area of the UPTD Public Health Center Sukaraya. It can be summarized that there is a relationship between diet and cholesterol levels in the elderly in the Sukaraya UPTD Health Center working area.